2020
DOI: 10.1097/md.0000000000019501
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine Shenqi compound to improve lower extremity atherosclerosis of patients with type 2 diabetes by affecting blood glucose fluctuation

Abstract: Background: Clinical and basic research supports that blood glucose fluctuation is an important predictor of diabetic vascular disease and an etiology of lower extremity atherosclerosis, which is an important pathological basis for lower extremity vascular diseases. Previous Chinese National Natural Science Foundation trials (No. 81503566) have reported that the traditional Chinese medicine Shenqi compound can reduce blood glucose fluctuation and low-grade inflammation, and protect blood vessels; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“… 15 Emerging evidence suggests that finding efficacious therapeutic drugs from TCM formulations could be an important strategy in DA cure. 16 In the present study, YQHX showed a remarkable effect against DA in vivo. First, ApoE-knockout mice were injected with streptozotocin and fed a high-fat diet: the blood glucose level, IR, TC level, and LDL-C level of mice in the model group increased significantly.…”
Section: Discussionsupporting
confidence: 56%
“… 15 Emerging evidence suggests that finding efficacious therapeutic drugs from TCM formulations could be an important strategy in DA cure. 16 In the present study, YQHX showed a remarkable effect against DA in vivo. First, ApoE-knockout mice were injected with streptozotocin and fed a high-fat diet: the blood glucose level, IR, TC level, and LDL-C level of mice in the model group increased significantly.…”
Section: Discussionsupporting
confidence: 56%
“…The abnormal glucose metabolism is another pathogenic factor of AS in addition to lipid metabolism. Available 6 Oxidative Medicine and Cellular Longevity evidence supports that blood glucose fluctuation is the etiology of lower extremity AS [137]. Although a direct causal relationship between elevated blood glucose and AS remains undefined, Tabit et al suggested that elevated blood glucose may act with the liver or adipose tissue and through these tissues influence the progression of AS [138,139].…”
Section: Effects Of Probiotics On Novel As Progression Factorsmentioning
confidence: 99%
“… 2015 ; Zhu et al. 2020 ) and has attracted considerable attention from scholars. TCM contains phytoestrogen, with numerous pharmacological effects, and has been applied for the therapeutic management of human diseases (Kiyama 2017 ).…”
Section: Introductionmentioning
confidence: 99%